Mild Hydrothermal Synthesis of Ni–Cu Nanoparticles. (29th June 2010) - Mohamed Saeed, G. H.; Radiman, S.; Gasaymeh, S. S.; Lim, H. N.; Huang, N. M.
Abstract : Magnetic Ni-rich Ni–Cu nanoparticles with Ni : Cu mass ratio ( S ) of 2.0 and 2.6 were prepared using a mixture of polyoxyethylene (10) isooctylphenyl ether (Triton X-100) and sodium dodecyl sulfate (SDS) in a mild hydrothermal condition at 95º C . X-ray diffractometry (XRD) showed that the nanoparticles prepared atS = 2 .0 possessed Ni–Cu alloy characteristic whereas the characteristic was absent atS = 2 .6 . The XRD data was enhanced by Fourier transform infrared spectroscopy (FTIR) which exhibited metal-metal (Ni–Cu) band at 455 cm − 1 . Based on transmission electron microscopy (TEM), the average particle sizes for the nanoparticles prepared atS = 2 .0 and 2.6 were in the range of 19–23 nm. The as-prepared nanoparticles exhibited paramagnetic behaviour measured using a vibrating sample magnetometer (VSM) and the specific saturation magnetization decreased at the higher concentration of Ni.